The Development of E-Sea book based on SAS method assisted with minimum competency assessment (akm) classroom efforts to improve vocabulary of low-grade students - Setyowati, Kiki; Purwati, Panca Dewi; Sismulyasih SB, Nugraheti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The goal of reading is to locate different types of information in a written material. To encourage reading habits, teachers must create engaging reading programs. However, researchers discovered that many children had poor reading skills based on observations made in class I of SDN Trimulyo 02 Semarang, which is where Teaching Campus 5 is located. Based on the pre-test the average is 67. based on the identification of issues brought on by a lack of resources for learning support, particularly media. Research on the usage of media, namely E- Sea Books, must be done using the Synthetic Structural Analytical (SAS) technique with support from the Class Minimum Competency Assessment (AKM). The purpose of this study is to use the SAS to evaluate the viability and efficacy of this media approach with help from AKM Class. The Research and Development (R&D) approach is applied in this study. An assessment questionnaire with a Likert scale was used to gather data on media suitability, and a Class AKM test instrument was used to examine effectiveness. According to the study's findings, the average media validity test score is 85% with respectable credentials, whereas the average material validity score is 90% with excellent qualities. The average knowledge value for the large-scale test was 96, whereas the average knowledge value for the small-scale effectiveness test was 92. There was a 29-percent increase in learning outcomes. The media created for common vocabulary was deemed viable and efficient based on the data analysis. utilized in SDN Trimulyo 02 Semarang's first-grade classroom.